Respon Kekebalan Pasca Imunisasi Hepatitis B Pada Anak Umur 4-6 Tahun - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT The objective of HB immunization is to protect people from Hepatitis B disease . The effect of those protection is showed that there is variation of amount of titre anti HBs when conducted the research . To increase the access of HB immunization and effective vaccination therefore the observation of the effectiveness of anti HBs after immunized to protect people after 3-5 years immunization could be analyzed. The present study was conducted to discover the amount of titre anti HBs for 4-6 years old children which had been immunized Hepatitis B when they were a baby (< lyear) The study was conducted with the designed of cross-section The subject is a 4-6 year old child at kindergarten school. The total sample is 94 children that divided into 2 groups. One groups is for children at completed immunization, another group is for children uncompleted immunization. Overall sample is conducted weight and height measure, mother and chid blood specimen test which obtain respond data of resistance after immunization Hepatitis B at 4-6 years old and mother Hepatitis status. The results are children 4-6 years which had been uncompleted immunized Hepatitis B when they were baby will have mean titre anti HBs 25,99 mlU/ml or 87% lower than children in the same age which have been completed Hepatitis B immunization have mean titre anti HBs 199,21 mlU/ml.